2009
DOI: 10.1007/s10384-009-0695-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 5-S-GAD on UV-B-induced cataracts in rats

Abstract: 5-S-GAD eyedrop application may delay the progression of UV-B-induced cataract in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Previously, UVC irradiation to induce turbidity of γ-crystallin was applied to measure the chaperone activity of lens γ-crystallin [24,25]. Lens γ-crystallin was correlated to cataracts and demonstrated in a mouse model [37].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, UVC irradiation to induce turbidity of γ-crystallin was applied to measure the chaperone activity of lens γ-crystallin [24,25]. Lens γ-crystallin was correlated to cataracts and demonstrated in a mouse model [37].…”
Section: Resultsmentioning
confidence: 99%
“…Eye drops containing antioxidants such as tropicamide, phenylephrine, flurbiprofen, and tobramycin are also given preoperatively [24]. In recent years, the protective effects of compounds against UV-induced oxidative damage of the eye were investigated [3,25,26]. It was shown that UV irradiation can cause turbidity of γ-crystallin [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…40 In our experiments, AST was administered to chicken eggs weighing about 60 g at the maximum dose of 100 mg, i.e. at a relatively high dose of 1.67 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, 5-S-GAD has been shown to have multiple activities including inhibition of some cancer cells in vitro and of angiogenesis in mice sarcoma cells in vivo, as well as protecting rat retinal ganglion cells against apoptosis induced by oxygen radicals and other conditions associated with glaucoma (Koriyama et al, 2009). Even more fascinating is that 5-S-GAD prevents cataract formation in the eye (Akiyama et al, 2009), so that it has potential as a pharmaceutical drug for use in eye drops (Kawada et al, 2009).…”
Section: Wound Disinfectionmentioning
confidence: 98%